Microqualification Programs at Universities: A New Educational Trajectory for Adult Education - M. O. Shepel; S. B. Veledinskaya; E. A. Diyskaya; A. V. Feshchenko; I. A. Korshunov; N. N. Shirkova (Высшее образование в России)
Traditional models of vocational education are decreasing their relevance due to rapid technological progress. The need to update skills and competencies leads to the emergence of new educational trajectories, including short programs for acquiring competencies to perform certain work functions and enter the labor market. The article examines the features of microqualification programs, their potential for employee training and their impact on the labor market. The analysis was carried out on the basis of data from the federal project “Employment Promotion”, data on vacancies on recruitment platforms and the results of focus groups with employers. Microqualification is interpreted as a set of highly specialized skills necessary to perform certain work functions that do not require a document on basic education. The authors of the article consider models based on the use of additional professional education and vocational training programs, as well as models that form individual educational trajectories within the framework of basic professional educational programs. An analysis of the salary data of participants in the federal project “Employment Promotion” shows that the passage of programs for the development of digital competencies provides a significant increase in wages after training. The results of the study demonstrate the high potential of microqualification programs for adult education and the formation of competitive specialists. The article offers recommendations on the implementation of microqualification programs in the Russian education system.